2013
DOI: 10.3109/01612840.2013.773473
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a brief Cognitive Behavioral Group Therapy for Psychological Distress among Female Icelandic University Students

Abstract: A study of a brief cognitive behavioral group therapy intervention for psychologically distressed Icelandic female university students was conducted using a pre-post test quasi-experimental design with intervention and control group conditions. Students were randomly allocated to control and intervention group conditions (n = 30). The intervention group received four sessions of cognitive behavioral group therapy, delivered by two advanced practice psychiatric nurses. Assessment of distress included self-repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 36 publications
2
14
0
1
Order By: Relevance
“…The quasi-experimental study showed that psychological distress decreased significantly in the intervention group (n = 19) compared to the control group (n = 11) post therapy. [8] This finding concurs with other more recent CBGT intervention studies which were also provided in four sessions for mildly depressed and/or anxious students. [43][44][45] The major finding of the qualitative study was that the participants evaluated the brief CBGT intervention favorably and felt their mood improved.…”
Section: Validation Of the Preliminary In-terventionsupporting
confidence: 81%
See 4 more Smart Citations
“…The quasi-experimental study showed that psychological distress decreased significantly in the intervention group (n = 19) compared to the control group (n = 11) post therapy. [8] This finding concurs with other more recent CBGT intervention studies which were also provided in four sessions for mildly depressed and/or anxious students. [43][44][45] The major finding of the qualitative study was that the participants evaluated the brief CBGT intervention favorably and felt their mood improved.…”
Section: Validation Of the Preliminary In-terventionsupporting
confidence: 81%
“…In the first step the effectiveness of the cognitive behavioral group therapy post intervention was evaluated with a quasi-experimental study (n = 30) and in the second step the acceptability of the intervention was evaluated with semi-structured interviews and a qualitative content analysis (n = 19). [8,10] Results of the validation of the preliminay intervention The validation of the intervention, based on two previous studies, showed positive results. The quasi-experimental study showed that psychological distress decreased significantly in the intervention group (n = 19) compared to the control group (n = 11) post therapy.…”
Section: Validation Of the Preliminary In-terventionmentioning
confidence: 99%
See 3 more Smart Citations